2017
DOI: 10.1075/jslp.3.1.01hac
|View full text |Cite
|
Sign up to set email alerts
|

Utilizing electropalatography to train palatalized versus unpalatalized consonant productions by native speakers of American English learning Russian

Abstract: Previous research has shown that English-speaking learners of Russian, even those with advanced proficiency, often have not acquired the contrast between palatalized and unpalatalized consonants, which is a central feature of the Russian consonant system. The present study examined whether training utilizing electropalatography (EPG) could help a group of Russian learners achieve more native-like productions of this contrast. Although not all subjects showed significant improvements, on average, the Russian le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(22 citation statements)
references
References 27 publications
0
21
1
Order By: Relevance
“…One group of learners was trained on /s/ vs. /s j /, while another group was trained on /t/ vs. /t j /. As mentioned in section 1.1 above, Hacking et al (2017) found that learners improved in the acoustic production of palatalized consonants as measured by changes in the second formant transitions of the adjacent vowel, but these relevant phonetic changes after training did not result in improved identification of palatalization by native Russian listeners. In terms of generalization, Hacking et al (2017) found no differences in production based on which pair a learner was trained on.…”
Section: Generalizationmentioning
confidence: 88%
See 2 more Smart Citations
“…One group of learners was trained on /s/ vs. /s j /, while another group was trained on /t/ vs. /t j /. As mentioned in section 1.1 above, Hacking et al (2017) found that learners improved in the acoustic production of palatalized consonants as measured by changes in the second formant transitions of the adjacent vowel, but these relevant phonetic changes after training did not result in improved identification of palatalization by native Russian listeners. In terms of generalization, Hacking et al (2017) found no differences in production based on which pair a learner was trained on.…”
Section: Generalizationmentioning
confidence: 88%
“…Schmidt (2012) reports similar results for 2 speakers of Korean on similar English contrasts. Hacking et al (2017) used EPG to train English-speaking learners of Russian to produce palatalized consonants, resulting in improvements to certain acoustic properties associated with palatalization but not in significant improvements in identification of these sounds by native Russian listeners. While these results are encouraging, the use of EPG as a feedback tool faces substantial hurdles in that the false palates must be custommade for each participant.…”
Section: Articulatory Feedback For L2 Speech Soundsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the studies in (Foote & McDonough, 2017;Huensch, 2016;Qian, Chukharev-Hudilainen, & Levis, 2018). They may also involve both face-to-face instruction and the use of technology (e.g., Hacking, Smith, & Johnson, 2016;Hardison, 2018;McCrocklin, 2019).…”
Section: Summary Of Key Components Of Teaching-oriented Papersmentioning
confidence: 99%
“…Non-technology interventions are especially valuable in showing how pronunciation instruction is successful in different instructional settings (e.g., learning Spanish word stress during a study abroad in Romanelli, Menegotto & Smyth, 2017). In the papers in Table 1, we find the use of oral corrective feedback with form-focused instruction (Lee & Lyster, 2016;Saeli, 2019); sensory-learning (Cerreta & Trofimovich, 2018); shadowing (Foote & McDonough, 2017); visualization of tone (Chun, Jiang, Meyr, & Yang, 2015); and the use of electropalatography to learn Russian palatal consonants (Hacking, Smith, & Johnson;.…”
Section: Summary Of Key Components Of Teaching-oriented Papersmentioning
confidence: 99%